Promosi Kesehatan Tentang Upaya Peningkatan Perilaku Hidup Bersih Melalui Penyuluhan Phbs Mencuci Tangan Guna Pencegahan Terjadinya Diare Di Batu Urip Lubuklinggau Utara II - Sari, Isra Purnama; Kurnia, Mutia Putri; sari, Tya Eka Purtama; Arifah, Detri Putri; Utami, Framanita; sari, Liya Lugita (Utami Publisher, 2024)
Health is the most important thing in human life and health is the keyword for early childhood happiness. This can be achieved with clean and healthy living behavior. Healthy living can be achieved by maintaining personal hygiene, and the easiest way to maintain personal hygiene is by washing your hands with soap. By getting used to clean and healthy living behavior, of course you can optimize the growth and development of children during the golden age. Clean and Healthy Living Behavior Development (PHBS) aims to build and preserve community behavior that focuses on cleanliness and health, so that the community can be independent in preventing and handling their own health problems. The aim is to increase public knowledge about good and correct hand washing. Based on the results of interviews with the people of Batu Urip sub-district, the problem is the low level of public knowledge about proper and correct hand washing. The method used in this activity is the method of educating the community about good and correct hand washing. The result of this activity is that public knowledge about a Clean and Healthy Lifestyle (PHBS) of good and correct hand washing has increased. Knowledge of recognizing good and correct hand washing is believed to be one of the most important factors for improving disease prevention. To increase this knowledge, it is provided Information about good and correct hand washing in the community needs to be provided so that the people of Batu Urip sub-district can understand the importance of maintaining bathing habits and personal hygiene.